Evaluating the intensity of the 'prompt' 140.5 keV γ-ray of 99Mo using a 4παβ(LS)-γ(HPGe) measurement system. (October 2022) - Nissim, S.; Aviv, O.; Brandis, M.; Weissman, L.; Sasson, R.; Yungrais, Z.; Datz, H.; Arazi, L.
Abstract: The absolute intensity for the 'prompt' 140.5 keV gamma-ray of 99 Mo was evaluated using the β-γ coincidence technique. A liquid sample of 99 Mo was prepared from a 99 Mo/ 99m Tc generator and measured in a 4παβ(LS)-γ(HPGe) system that comprises a Liquid Scintillator (LS) detector and a High-Purity Germanium (HPGe) detector. The sample was introduced into scintillation fluid embedded in a photo-reflector assembly that provides almost 100% efficiency for detecting β particles (in the energy range of intreset). The combination of the HPGe and the LS detectors provided a highly effective rejection mechanism for non-coincident events. Thereby, the distinction between the detected 140.5 keV events originating from decays of 99m Tc (IT) and those from transitions bypassing the metastable state could be obtained and the 'prompt' intensity was evaluated directly. The system was calibrated for detecting β particles and γ-rays using radioactive sources of known activities and having identical geometry as the sample containing 99 Mo. The absolute intensity of the 'prompt' 140.5 keV was found to be (5.21 ± 0.02stat ±0.16sys )%, in good agreement with results from more recently reported works. Highlights: The intensity of 140.5-keV gamma-ray emitted from 99 Mo was evaluated using a β-γ measurement system. Result is in agreement with values from more recent experimental works. Measurement uncertainty is competitive with other more traditional methods. The method is applicable to other parent/daughter radionuclides with interfering lines.